DSM-5 and ICD-11 alcohol use disorder criteria in young adult regular drinkers: Lifetime prevalence and age of onset. (1st December 2021) - Slade, Tim; Mewton, Louise; O'Dean, Siobhan; Tibbetts, Joel; Clay, Peter; Isik, Ashling; Johnson, Phoebe; McCraw, Stacey; Upton, Emily; Kypri, Kypros; Butterworth, Peter; McBride, Nyanda; et al.
Abstract: Background: Alcohol Use Disorder (AUD) is a significant contributor to global disease burden. AUD has a relatively early onset during young adulthood (Teesson et al., 2010). However, compared to AUD in adults, we have relatively little understanding of AUD in adolescents and emerging adults. Methods: The RADAR study is a prospective cohort study designed to investigate the emergence of AUD in community-dwelling adolescents and emerging adults across Australia (age range = 18–21 at baseline). At 6 monthly intervals over 2.5 years, participants were interviewed regarding alcohol consumption and alcohol use disorder criteria by clinical psychologists using the SCID-IV-RV. This paper reports the baseline findings of the RADAR cohort. Results: Proportions of lifetime criteria endorsement among regular drinkers varied considerably. Tolerance was the most endorsed criterion (50.3%), followed by Social Problems (10.4%) and Larger/Longer (9.0%). The median age of onset for most individual AUD criteria was 18 years of age. 18.4% of our cohort met DSM-5 AUD diagnosis in their lifetime to date, and 16.8% met ICD-11 dependence. When removing Tolerance from the AUD criteria, DSM-5 AUD lifetime prevalence reduced to 11.0%, and ICD-11 AUD lifetime prevalence fell to 7.1% in our cohort. Conclusions: Variable rates of criteria endorsement likely reflect both true differences in the experience of AUD criteria and methodological challenges in the assessment of AUD in an emerging adult age group. High rates of tolerance to the effects of alcohol, and relatively low rates of drinking larger/longer than intended are discussed considering methodological challenges in assessing these criteria in young adults. Highlights: Baseline findings from a longitudinal cohort study examining alcohol use disorder criteria in young adult regular drinkers. 18.4% met DSM-5 AUD diagnosis in their lifetime to date, and 16.8% met ICD-11 dependence. Rates of lifetime AUD criteria endorsement varied considerably. Tolerance to the effects of alcohol was the most commonly endorsed criteria. Minimal gender differences in endorsement and age of onset of AUD criteria.